Molecular Alterations in Semen of Per-And Polyfluoroalkyl Substance Exposed Subjects: Association Between DNA Integrity, Antioxidant Capacity and Lipoperoxides - Marinaro, Carmela; Bianchi, Anna Rita; Guerretti, Valeria; Barricelli, Gaia; Berman, Bruno; Bertola, Francesco; Micali, Salvatore; Busardò, Francesco Paolo; Di Giorgi, Alessandro; De Maio, Anna; Piscopo, Marina; Montano, Luigi; et al. (Antioxidants, 2025)
In the last decades, there has been huge interest in Per- and Polyfluoroalkyl Substances (PFAS) worldwide because of the toxic effects on humans. In 2013, a large-scale contamination of PFASs in the Veneto region was caused by a fluorochemical plant in Vicenza. About 130,000 inhabitants were exposed to PFAS in their drinking water. To date, relatively few studies have investigated the associations between blood serum PFAS concentrations and oxidative stress in semen. This study compared the antioxidant activity, lipoperoxide levels and protection or induction of oxidative DNA damage by sperm nuclear basic proteins (SNBP) in subjects living in Veneto exposed to PFAS (VNT) with those living in a non-PFAS contaminated area (VSL). Although the semen parameters were within the WHO range, the VNT semen samples showed higher levels of lipoperoxides and lower antioxidant activity compared to the VSL samples. These differences were statistically significant. We also examined DNA damage following SNBP addition under pro-oxidative conditions, finding a significantly different distribution of DNA damage types between the two groups, where 0 means no damage and 1 to 3 means increasing damage with 3 indicating maximum damage. SNBP of VNT subjects showed a reduced ability to protect DNA from oxidative damage. In the VSL group, damage 0 was found in 56% of subjects, 35% of the VNT group show damage 1, 36% damage 2 and 18% damage 3, while only 11% of VNT subjects show damage 0. Additionally, VNT with 0-grade DNA oxidative damage also exhibited reduced antioxidant activity and higher levels of lipoperoxides, in contrast to VSL. The results of this study indicate that exposure to PFAS produces oxidative stress in the semen of VNT subjects, who were also found to have blood serum perfluorooctanoic acid (PFOA) levels above the threshold. This suggests the possibility of infertility issues and emphasises the necessity for additional research into the long-term consequences of oxidative stress on male fertility and the health of offspring.